Effect of liraglutide, a glucagon‐like peptide‐1 analogue, on left ventricular function in stable chronic heart failure patients with and without diabetes (LIVE)—a multicentre, double‐blind, randomised, placebo‐controlled trial. (28th October 2016) - Jorsal, Anders; Kistorp, Caroline; Holmager, Pernille; Tougaard, Rasmus Stilling; Nielsen, Roni; Hänselmann, Anja; Nilsson, Brian; Møller, Jacob Eifer; Hjort, Jakob; Rasmussen, Jon; Boesgaard, Trine Welløv; Schou, Morten; et al.
Abstract : Aims: To determine the effect of the glucagon‐like peptide‐1 analogue liraglutide on left ventricular function in chronic heart failure patients with and without type 2 diabetes. Methods and results: LIVE was an investigator‐initiated, randomised, double‐blinded, placebo‐controlled multicentre trial. Patients ( n = 241) with reduced left ventricular ejection fraction (LVEF ≤45%) were recruited (February 2012 to August 2015). Patients were clinically stable and on optimal heart failure treatment. Intervention was liraglutide 1.8 mg once daily or matching placebo for 24 weeks. The LVEF was similar at baseline in the liraglutide and the placebo group (33.7 ± 7.6% vs. 35.4 ± 9.4%). Change in LVEF did not differ between the liraglutide and the placebo group; mean difference (95% confidence interval) was −0.8% (−2.1, 0.5; P = 0.24). Heart rate increased with liraglutide [mean difference: 7 b.p.m. (5, 9), P < 0.0001]. Serious cardiac events were seen in 12 (10%) patients treated with liraglutide compared with 3 (3%) patients in the placebo group ( P = 0.04). Conclusion: Liraglutide did not affect left ventricular systolic function compared with placebo in stable chronic heart failure patients with and without diabetes. Treatment with liraglutide was associated with an increase in heart rate and more serious cardiac adverse events, and this raises some concern with respect to the use of liraglutide in patients with chronic heart failure and reduced left ventricular function. More data on the safety of liraglutide in different subgroups of heart failure patients are needed.